2021
DOI: 10.1103/physrevmaterials.5.044202
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the flat bands of the kagome metal CoSn with Fe, In, or Ni doping

Abstract: CoSn is a Pauli paramagnet with relatively flat d-bands centered about 100 meV below the Fermi energy, EF. Single crystals of CoSn lightly doped with Fe, In or Ni are investigated using x-ray and neutron scattering, magnetic susceptibility and magnetization, ac susceptibility, specific heat and resistivity measurements. Within the rigid band approximation, hole doping with a few percent of Fe or In should move the flat bands closer to EF, whereas electron doping with Ni should move the flat bands further away … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…As noted above, CoSn is a Pauli paramagnet, and In substitution up to 20% has been shown to increase the overall magnetic moment, 28 consistent with the electronic structure response just described. However, no new ground state was observed at that modest In content.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…As noted above, CoSn is a Pauli paramagnet, and In substitution up to 20% has been shown to increase the overall magnetic moment, 28 consistent with the electronic structure response just described. However, no new ground state was observed at that modest In content.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
“…Previously, we found that adding Fe to CoSn did add holes and moved the flat bands closer to E F , but each Fe appeared to carry a local magnetic moment of about 2 μ B that dominated the magnetic response and obscured any subtle effects from the flat bands. 28 Indium doping was limited in that study to concentrations up to 20%. The results indicated an approach toward a flat band-related instability with increasing In content but revealed no associated phase transition.…”
Section: ■ Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Two of the seven studied compounds have been previously reported to be magnetically ordered. The magnetic moments on Fe atoms are aligned ferromagnetically (FM) in FeGe [86,87], while in FeSn the antiferromagnetic (AFM) order is observed [88]. In AFM structure the spins are arranged ferromagnetically in each FeSn layer and antiferromagnetically ordered in neighboring layers.…”
Section: Resultsmentioning
confidence: 99%